Práticas inovadoras na educação física escolar : possibilidades pedagógicas no ensino de lutas com alunos do 9º ano do ensino fundamental - Silva, Plíneo Augusto de Souza e (2024)
This research addressed the thematic unit of fighting based on innovative practices in Physical Education. In this sense, the main objective of this work was to analyze the development of teaching Body Fighting, based on innovative practices, to students in the 9th grade of Elementary School. The choice of this content is justified mainly because it presents itself as an element of body culture that contemplates the characteristics of innovative practices in School Physical Education, since it goes beyond traditional sports and offers conditions for working on classes that place the student at the center of the learning process. In addition, fighting was often excluded from the EFE curriculum, with teachers alleging concerns related to violence, lack of specific knowledge about fighting modalities and gender stereotypes. The dissertation sought to analyze the transformation of School Physical Education in Brazil, especially after the redemocratization after the military dictatorship. The research used a qualitative approach, being an intervention research type, and was conducted with 24 adolescents in the 9th grade of Elementary School, aged between 14 and 16 years old, at the 9 de Julho State School in Água Boa, Mato Grosso do Sul. A diagnostic questionnaire and an exit questionnaire were used as data collection instruments to establish a comparison with the first questionnaire, observing whether there was a change in understanding after the development of the didactic sequence. The classes addressed the history and concepts of fighting, in addition to promoting practical experiences of fighting games and specific techniques. The research culminated in Taekwondo, Jiu-jitsu and Capoeira workshops, taught by local professionals, in which the students were the protagonists. The results indicate that the innovative approach was well received by the students, evidenced by the high participation rate and the positive change in the perception of CL, contrasting with the previous view that these practices were associated with violence. The teaching sequence also highlighted the benefits of CL for the integral development of students, going beyond simple physical improvement, integrating critical, cultural and social aspects. It was found that the inclusion of CL in Physical Education classes, through innovative practices, is viable and enhances the formation of critical and inclusive citizens, contributing to a more democratic and equitable education.